2019
DOI: 10.30757/alea.v16-32
|View full text |Cite
|
Sign up to set email alerts
|

Poisson statistics at the edge of Gaussian beta-ensemble at high temperature

Abstract: We study the asymptotic edge statistics of the Gaussian β-ensemble, a collection of n particles, as the inverse temperature β tends to zero as n tends to infinity. In a certain decay regime of β, the associated extreme point process is proved to converge in distribution to a Poisson point process as n → +∞. We also extend a well known result on Poisson limit for Gaussian extremes by showing the existence of an edge regime that we did not find in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For local statistics, in [7], the bulk eigenvalues are shown to exhibit Poissonian statistics by inspecting the correlation functions under the assumption nβ = γ ≥ 0. The corresponding result for the edge in the regime nβ 1 is treated by same means in [14]. Later, the bulk result for nβ = γ ≥ 0 is retrieved by Minami's method in [13] and an extension of the CLT to this new regime is introduced.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For local statistics, in [7], the bulk eigenvalues are shown to exhibit Poissonian statistics by inspecting the correlation functions under the assumption nβ = γ ≥ 0. The corresponding result for the edge in the regime nβ 1 is treated by same means in [14]. Later, the bulk result for nβ = γ ≥ 0 is retrieved by Minami's method in [13] and an extension of the CLT to this new regime is introduced.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…for some constant λ P α , see [35,Lemma 3.2] for example. The fluctuations of the eigenvalues in the bulk and at the edge of a configuration were studied for example in [8,47,57,58,61]. These fluctuations were shown to be described by Poisson statistics in this regime.…”
Section: The Toda Chain's Currentsmentioning
confidence: 99%
“…On the other hand, in [19,59,60] the authors reconstruct the densities from the moment generating functions. Several authors [12,38,44,45,48,61] investigated the local fluctuations of the eigenvalues, they observed that in this regime they are described by a Poisson process. In particular, in [38] Lambert studied the local fluctuations for general Gibbs ensembles on N -dimensional manifolds, moreover he also studied the asymptotic behaviour of the maximum eigenvalue for the classical beta ensemble at high-temperature.…”
Section: Circular Beta Ensemble At High-temperaturementioning
confidence: 99%